Pengaruh Konten Instagram Food Vlogger @gina_angelia terhadap Minat Kuliner pada Followers - Febrianita, Rika Hadhi; Nursanti, Siti; Utamidewi, Wahyu (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instagram is one of the most popular forms of social media used for information, communication, and entertainment, with a wide reach and a continuously growing user base. The Instagram food vlogger account @gina_angelia has gained popularity among individuals due to its unique culinary content. This research aims to determine the influence of @gina_angelia's Instagram content on culinary interests among her followers. The study adopts a quantitative approach using the AIDDA theory, with data collected through a questionnaire from 100 respondents. The results of this research indicate that @gina_angelia's Instagram content significantly influences the culinary interests of her followers, with a coefficient of determination value of 72.1%. The remaining 27.9% is influenced by other variables outside the model. The results, processed using SPSS 26, reveal that the sub-variable X, namely Attention to @gina_angelia's Instagram content, significantly affects the culinary interest of her followers. Interest in @gina_angelia's Instagram content also significantly impacts on her followers' culinary interests. Likewise, Desire in @gina_angelia's Instagram content significantly influences her followers' culinary interests. The Decision factor shows that @gina_angelia's Instagram content has a significant influence on her followers' culinary interests. Meanwhile, the Action factor indicates that @gina_angelia's Instagram content significantly influences her followers' culinary interests. Keywords: Instagram, Culinary Interests, Food Vlogger